Apelin protects auditory cells from cisplatin-induced toxicity in vitro by inhibiting ROS and apoptosis. (29th May 2020) - Yin, Haiyan; Zhang, Hui; Kong, Youhua; Wang, Chunmei; Guo, Yan; Gao, Yang; Yuan, Lili; Yang, Xinxin; Chen, Jing
Highlights: Cisplatin down-regulates Apelin expression in HEI-OC1 cells and cochlear hair cells. Apelin protects HEI-OC1 cells and cochlear hair cells from cisplatin-induced injury in vitro. Apelin attenuates cisplatin-induced ROS and apoptosis in HEI-OC1 cells and hair cells in vitro. Abstract: Apelin, a specific endogenous ligand of the G protein-coupled receptor APJ, suppresses oxidative stress and apoptosis in vitro and in vivo . The current study explored whether Apelin protects against toxicity induced by the anticancer drug cisplatin in vitro, and the possible mechanisms that underlie this protective effect. The results showed that Apelin was expressed in the mouse auditory cell line HEI-OC1 and in cochlear hair cells (HCs) and was significantly downregulated by cisplatin, whereas pre-treatment with exogenous Apelin significantly reduced cisplatin-induced apoptosis, and thus protected HEI-OC1 cells and cochlear HCs from cisplatin-induced injury. Furthermore, Apelin reduced reactive oxygen species (ROS) generation, rescued mitochondrial membrane potential disruption, inhibited JNK signaling and attenuated the expression of pro-apoptotic factors in HEI-OC1 cells and in cochlear explants treated with cisplatin. Our findings suggest that Apelin could be used as an otoprotective agent for the prevention of cisplatin-induced ototoxicity.